Modeled approaches to estimating blue carbon accumulation with mangrove restoration to support a blue carbon accounting method for Australia - Catherine E. Lovelock; M. Fernanda Adame; Don W. Butler; Jeffrey J. Kelleway; Sabine Dittmann; Benedikt Fest; Karen J. King; Peter I. Macreadie; Katherine Mitchell; Mark Newnham; Anne Ola; Christopher J. Owers; et al. (Limnology and Oceanography, 2022)
The development and refinement of methods for estimating organic carbon accumulation in biomass and soils during mangrove restoration and rehabilitation can encourage uptake of restoration projects for their ecosystem services, including those of climate change mitigation, or blue carbon. To support the development of a blue carbon method for Australia under the Emission Reduction Fund scheme we investigated; (1) whether carbon accumulation data from natural mangroves could be used to estimate carbon accumulation during restoration; (2) modeling mangrove biomass accumulation; and (3) how modeled carbon accumulation could be achieved over heterogeneous sites. First, we assessed carbon accumulation in soil and biomass pools from the global literature, finding that estimating carbon accumulation using data from natural mangroves provided similar estimates as those for restored or rehabilitated mangroves. We assessed mangrove biomass accumulation from global chronosequence studies, which we used to develop regional models for estimating biomass accumulation with restoration in Australia using values from local natural mangroves. Estimating biomass carbon accumulation using site‐based means of stand biomass provided similar estimates as values estimated through use of regional means values stratified by elevation; and reduced overestimates of biomass carbon accumulation that were based on regional mean values. Modeling soil carbon accumulation over environmentally heterogeneous project sites can apply a similar approach, stratifying over variation in site elevation. Our analysis provides a strategy for modeling blue carbon pools for an Australian blue carbon method that accommodates regional differences and is based on data from natural mangroves.

How does clay constrain woody biomass in drylands? - Roderick J. Fensham; Don W. Butler; Jenny Foley (Global Ecology and Biogeography, 2015)
Aim To investigate the role of clay in limiting the development of woody biomass in drylands. Location A ustralia. Methods Spatial data representing woody biomass, soil clay content and climate for the A ustralian continent were interpreted to explore the relationship between a moisture index and woody biomass on clay and non‐clay substrates. Moisture and soil water potential were investigated through time for clay and sand plains. Sub‐soil clay and other soil characteristics were compared between areas with and without high tree mortality after drought. Results The substantially lower woody biomass on clay soils than non‐clay soils in the drylands of the A ustralian continent verifies the inverse texture effect. A clay floodplain consistently held more water than an adjacent sandplain, but soil moisture in the clay was effectively inaccessible to plants for much longer periods because of more negative values of water potential in the clay soil. Small increases in sub‐soil clay were associated with high tree mortality. Main conclusions Our findings suggest that the ‘inverse texture effect’, which describes the negative association of woody biomass with soil clay content in drylands, may mostly relate to the moisture‐retentive properties of clay rather than being caused by reduced infiltration and enhanced evaporation from clay‐rich soils. Our evidence suggests that clay soils constrain woodiness in drylands by exacerbating water stress, and confirm the fundamental role of aridity in determining woody biomass and the global distribution of grassland.

Aborigine‐managed forest, savanna and grassland: biome switching in montane eastern Australia - Don W. Butler; Roderick J. Fensham; Brett P. Murphy; Simon G. Haberle; Sarah J. Bury; David M. J. S. Bowman (Journal of Biogeography, 2014)
Aim To assess hypotheses about the role of anthropogenic fire in the maintenance and origin of a fine‐scale vegetation mosaic of rain forest, eucalypt savanna and grassland. Location Bunya Mountains, subtropical eastern Australia. Methods A time series of vegetation maps was compiled from historical and recent aerial photography and field surveys. Geospatial models were constructed of environmental domains for rain forest, savanna and grassland, and for areas of biome change. Grassland soils were analysed for carbon isotope ratios (δ 13 C), and radiocarbon ( 14 C) dates were acquired for bulk samples from a range of depths. Results Analysis revealed weak associations between topography and the distribution of rain forest, savanna and grassland, and their patterns of recent change. Grassland occupied an environmental domain intermediate between rain forest and savanna and was more than four times as likely to occur within a matrix of rain forest rather than savanna. There was a large proportional reduction in the area of both grassland (−35%) and savanna (−19%) between 1961 and 2006 because of the expansion of rain forest. However, the greater initial extent of savanna meant that the areal loss of savanna was an order of magnitude greater than for grassland (1433 vs. 146 ha). There was no evidence of abrupt changes in δ 13 C in grassland soil profiles, indicating stability of the vegetation over the last 2000 years. Main conclusions There is no simple gradient in ‘tree suitability’ from rain forest, through savanna, to treeless grassland on the Bunya Mountains. A general absence of fire since the 19th century has greatly reduced the extent of grassy savanna and grassland formations, to the advantage of rain forest. These results support the hypothesis that the vegetation mosaic on the Bunya Mountains is a cultural artefact and testament to millennia of skilful and persistent burning. We could not conclusively reject the hypothesis that the grasslands are Pleistocene relicts that have declined throughout the Holocene; nonetheless, an explanation more consistent with the evidence overall is that the grasslands must have had periods of expansion during the Holocene, probably as a consequence of severe fires that have destroyed patches of rain forest.

Setbacks to shoot growth are common in woody plants, so how are shoots of some species safer than others? - Don W. Butler; Sean M. Gleason; Mark Westoby (Ecology, 2012)
Tissue turnover is a critical facet of plant life history variation. This study quantifies losses from setbacks to growth of terminal woody shoots 1.2 m long, across 83 species and seven sites in eastern Australia. Setbacks, where the leading meristem had been removed or died and a new leader had emerged, were common (median three per shoot). Shoots had lost an average of 0.25 m of lead‐stem length for 1.2 m net shoot‐length gain. Insects like girdlers and borers were prominent causes of large setbacks. The sites spanned tropical to temperate and humid to semiarid climates, but variation in stem loss was much greater across species than across sites. We measured 17 plant functional traits related to growth form, mechanics, hydraulics, and economics. Only four traits were correlated with variation across species in stem losses: stem diameter, stem nitrogen content, bark thickness, and maximum photosynthetic rate. The correlations were weak. Stem specific gravity (wood density) showed no correlation with risk. Our results suggest a pattern similar to the growth–risk trade‐off known for herbaceous plants, where traits associated with fast growth increase tissue turnover and herbivory, but the weak correlations leave ample scope for other influences that remain to be identified.